Manufacturing process of highlight PET (Polyethylene Terephthalate) film

By adding an appropriate amount of light stabilizer and heat stabilizer to the PET film manufacturing process, the problem of insufficient light transmittance of the PET film is solved, significantly improves the light transmittance, meets the high standard requirements of electronic products, and expands the scope of application of the PET film.

CN119875174APending Publication Date: 2025-04-25GUANGDONG LAIRUIBAO TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510165971.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The light transmittance of the PET film produced by the existing PET film manufacturing process is not ideal enough and cannot meet the high standards in the field of electronic products, resulting in a reduced adaptability range of the PET film.

Method used

By adding a suitable proportional ratio light stabilizer and a thermal stabilizer to the manufacturing process of the PET film, the light transmittance of the PET film is improved. Specific steps include raw material installation, pretreatment, curing, surface modification, cross-linking reaction, improving light transmittance, granulation, film formation and winding molding.

Benefits of technology

The light transmittance of the PET film is significantly improved, the light transmittance of the PET film is enhanced, so that it can meet the high standard requirements of existing electronic products, and effectively improve the adaptability range of the PET film.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a manufacturing process of a high-gloss PET (polyethylene terephthalate) film, which comprises the following steps: step S1, raw material preparation: raw materials are weighed and prepared according to raw material components required by the preparation process, and the weighed raw materials comprise 30-50wt% of polyethylene glycol terephthalate, 10-20wt% of heat insulation master batch, 10-20wt% of polyethylene and 8-16wt% of polyethylene naphthalate; the coating is prepared from, by weight, 8%-15% of polyurethane, 2%-6% of sodium tripolyphosphate, 1%-5% of an antioxidant, 4%-14% of polyacrylate resin, 1%-6% of a heat stabilizer, 2%-8% of a curing agent, 2%-7% of a coupling agent, 2%-10% of polyethylene glycol, 0.5%-3% of a slipping agent and 0.5%-5% of a light stabilizer. By adding the light stabilizer and the heat stabilizer in a proper ratio, the light transmittance of the prepared PET film is greatly improved, and the light transmittance of the PET film is enhanced, so that the high-standard requirements of existing electronic products can be met, and the application range of the PET film is effectively widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PET films, in particular to a manufacturing process of a high-gloss PET film. Background Art

[0002] PET film, also known as high temperature resistant polyester film, has excellent physical and chemical properties, dimensional stability and recyclability. It can be widely used in magnetic recording, photosensitive materials, electronics, electrical insulation, industrial films, packaging decoration, screen protection, optical mirror surface protection and other fields. With the development of special functional films, new uses of polyester film are constantly emerging. It can be produced into mobile phone LCD protective film, LCD TV protective film, mobile phone keypad and other products. PET film is a packaging film with relatively comprehensive performance. It has good transparency and gloss; good air tightness and fragrance retention; medium moisture resistance, and the moisture permeability decreases at low temperatures. PET film has excellent mechanical properties, and its toughness is the best among all thermoplastics. The tensile strength and impact strength are much higher than those of ordinary films; and it has good strength and dimensional stability, which is suitable for secondary processing such as printing and paper bags. PET film also has excellent heat resistance, cold resistance, good chemical resistance and oil resistance.

[0003] As the quality requirements of electronic products gradually increase, the process requirements for PET films are also gradually increasing. The light transmittance of PET films produced by the manufacturing process used in existing PET films is not ideal, and the performance cannot meet the high standards required in the field of electronic products, resulting in a reduction in the adaptability of PET films. Summary of the invention

[0004] The purpose of the present invention is to provide a method to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a manufacturing process of a high-gloss PET film, comprising the following steps: Step S1, raw material preparation: weigh and prepare raw materials according to the raw material components required by the preparation process, and the weighed raw materials include: 30-50wt% of polyethylene terephthalate, 10-20wt% of thermal insulation masterbatch, 10-20wt% of polyethylene, 8-16wt% of polyethylene naphthalate, 8-15wt% of polyurethane, 2-6wt% of sodium tripolyphosphate, 1-5wt% of antioxidant, 4-14wt% of polyacrylate resin, 1-6wt% of heat stabilizer, 2-8wt% of curing agent, 2-7wt% of coupling agent, 2-10wt% of polyethylene glycol, 0.5-3wt% of lubricant and 0.5-5wt% of light stabilizer; Step S2, raw material pretreatment: adding 30-50wt% of polyethylene terephthalate, 10-20wt% of thermal insulation masterbatch, 10-20wt% of polyethylene, 8-16wt% of polyethylene naphthalate, 8-15wt% of polyurethane, 2-6wt% of sodium tripolyphosphate, 4-14wt% of polyacrylate resin and 2-10wt% of polyethylene glycol to a mixing device for stirring and mixing; Step S3, material curing: adding 2-8 wt% of curing agent to the mixing device in step S2 for curing, the curing agent accelerates the curing of the mixed material, and adding 1-5 wt% of antioxidant during the curing process; Step S4, surface modification: adding 2-7 wt% of coupling agent to the mixture obtained in step S3, and performing surface modification on the mixture with 2-7 wt% of coupling agent, so as to obtain a mixture raw material with reduced viscosity; Step S5, cross-linking reaction: adding 0.5-3 wt% of a lubricant to the mixed raw material obtained in step S4, so that the mixed raw material undergoes a cross-linking reaction to generate a smooth mixed raw material; Step S6, improving light transmittance: adding 0.5-5wt% of light stabilizer and 1-6wt% of heat stabilizer to the mixed raw material obtained in step S5 to improve the light transmittance of the mixed raw material; Step S7, granulation: conveying the mixture obtained in step S6 to an extruder for extrusion, and then pelletizing it through a pelletizer to obtain granular high-transmittance PET particles; Step S8, film forming: the high-transmittance PET particles obtained in step S7 are stretched transversely and longitudinally through a fully automatic vacuum drum, an extruder and a biaxial stretching unit to obtain a formed high-gloss PET film; Step S9, rolling and forming: cutting and trimming the high-gloss PET film dried in step S8, rolling up the cut high-gloss PET film and storing it, thereby completing the manufacturing of the high-gloss PET film.

[0006] Furthermore, the manufacturing method of the thermal insulation masterbatch is as follows: first prepare 60wt% of cesium tungstate powder, add 80wt% of the prepared cesium tungstate powder, 5wt% of polyacrylate resin and 7wt% of coupling agent into a mixing and stirring device, mix and stir evenly, feed the mixed material into an extruder, and the material is extruded through the die head of the extruder after preheating, heating to melt, devolatilization and shearing, and then cooled into a solid state by a cooling device and enters a pelletizer for cutting to make a thermal insulation masterbatch.

[0007] Furthermore, the antioxidant is selected from any one or more of tea polyphenols, tocopherol, butylated hydroxyanisole, butylated hydroxytoluene or tert-butylhydroquinone.

[0008] Furthermore, the mixing temperature of step S2 is controlled between 125° C. and 150° C., and the mixing time of step S2 is controlled between 1 h and 1.5 h.

[0009] Furthermore, the light stabilizer is specifically one or more of carbon black, titanium dioxide benzophenone, salicylic acid ester and benzotriazole.

[0010] Furthermore, the film forming temperature in step S8 is controlled between 100° C. and 120° C., and the high-gloss PET film in step S9 needs to be cooled to below 25° C. before being rolled up.

[0011] Furthermore, the lubricant is selected from any one or more of oleamide, erucamide, calcium stearate and silicone.

[0012] Furthermore, the coupling agent is specifically a mixture of silane coupling agent a151 and vinyltrimethoxysilane, and the mixing weight ratio of the silane coupling agent a151 and vinyltrimethoxysilane is 1:1.

[0013] Furthermore, the thermal stabilizer is triethyl phosphate.

[0014] Furthermore, the curing agent is one or more of diaminodiphenylmethane, m-phenylenediamine, and diaminodiphenyl sulfone.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention significantly improves the light transmittance of the prepared PET film by adding a light stabilizer and a heat stabilizer in a suitable ratio, thereby enhancing the light transmittance of the PET film, so that the products processed from the PET film have excellent light transmittance, thereby being able to meet the high standard requirements of existing electronic products, and effectively improving the adaptability of the PET film. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1 The present invention provides a manufacturing process of a high-gloss PET film, comprising the following steps: Step S1, raw material preparation: weigh and prepare the raw materials according to the raw material components required by the preparation process, and the weighed raw materials include: 30wt% of polyethylene terephthalate of model Huizhou Nanya 4210G3, 10wt% of thermal insulation masterbatch, 15wt% of linear low-density polyethylene 1002, 8wt% of polyethylene naphthalate of TeonexQ65, 8wt% of thermoplastic polyurethane ShoreD55, 2wt% of sodium tripolyphosphate, 5wt% of antioxidant, 6wt% of Paraloid series thermoplastic polyacrylate resin, 4wt% of heat stabilizer, 3wt% of curing agent, 2wt% of coupling agent, 2wt% of low molecular weight polyethylene glycol 4000, 3wt% of lubricant and 2wt% of light stabilizer; Step S2, raw material pretreatment: adding 30wt% of Huizhou Nanya 4210G3 polyethylene terephthalate, 10wt% of thermal insulation masterbatch, 15wt% of linear low-density polyethylene 1002, 8wt% of TeonexQ65 polyethylene naphthalate, 8wt% of thermoplastic polyurethane ShoreD55, 2wt% of sodium tripolyphosphate, 6wt% of Paraloid series thermoplastic polyacrylate resin and 2wt% of low molecular weight polyethylene glycol 4000 to a mixing device for stirring and mixing; Step S3, material curing: adding 3wt% of curing agent to the mixing device in step S2 for curing, the curing agent accelerates the curing of the mixed material, and adding 5wt% of antioxidant during the curing process; Step S4, surface modification: adding 2 wt% of coupling agent to the mixture obtained in step S3, and performing surface modification on the mixture with 2 wt% of coupling agent, so as to obtain a mixture raw material with reduced viscosity; Step S5, cross-linking reaction: adding 3 wt% of a lubricant to the mixed raw material obtained in step S4, wherein 3 wt% of the lubricant causes the mixed raw material to undergo a cross-linking reaction to generate a smooth mixed raw material; Step S6, improving light transmittance: adding 2 wt% of light stabilizer and 4 wt% of heat stabilizer to the mixed raw material obtained in step S5 to improve the light transmittance of the mixed raw material; Step S7, granulation: conveying the mixture obtained in step S6 to an extruder for extrusion, and then pelletizing it through a pelletizer to obtain granular high-transmittance PET particles; Step S8, film forming: the high-transmittance PET particles obtained in step S7 are stretched transversely and longitudinally through a fully automatic vacuum drum, an extruder and a biaxial stretching unit to obtain a formed high-gloss PET film; Step S9, rolling and forming: cutting and trimming the high-gloss PET film dried in step S8, rolling up the cut high-gloss PET film and storing it, thereby completing the manufacturing of the high-gloss PET film.

[0018] The manufacturing method of the thermal insulation masterbatch is as follows: first prepare 60wt% of cesium tungstate powder, add 80wt% of the prepared cesium tungstate powder, 5wt% of Paraloid series thermoplastic polyacrylate resin and 7wt% of coupling agent into a mixing and stirring device, mix and stir evenly, feed the mixed material into an extruder, and extrude the material through the die head of the extruder after preheating, heating and melting, devolatilization and shearing, and then cool it into a solid state through a cooling device and enter a pelletizer for cutting to prepare the thermal insulation masterbatch.

[0019] The antioxidant is a mixture of tea polyphenols, tocopherol and butylated hydroxyanisole, and the mixing weight ratio of tea polyphenols, tocopherol and butylated hydroxyanisole is 1:2:1.

[0020] The mixing temperature of step S2 is controlled at 130° C., and the mixing time of step S2 is controlled at 1 hour.

[0021] The light stabilizer is specifically a mixture of carbon black, titanium dioxide benzophenone and salicylate, and the mixing weight ratio of carbon black, titanium dioxide benzophenone and salicylate is 1:1:1.

[0022] The film forming temperature in step S8 is controlled at 100° C., and the high gloss PET film in step S9 needs to be cooled to below 25° C. before being rolled up.

[0023] The lubricant is a mixture of oleamide, erucamide and calcium stearate, and the weight ratio of oleamide, erucamide and calcium stearate is 1:1:1.

[0024] The coupling agent is specifically a mixture of silane coupling agent a151 and vinyl trimethoxy silane, and the mixing weight ratio of the silane coupling agent a151 and vinyl trimethoxy silane is 1:1.

[0025] The thermal stabilizer is triethyl phosphate.

[0026] The curing agent is a mixture of diaminodiphenylmethane, metaphenylenediamine and diaminodiphenyl sulfone, and the mixing weight ratio of diaminodiphenylmethane, metaphenylenediamine and diaminodiphenyl sulfone is 1:2:1.

[0027] Example 2 The difference from the embodiment 1 is that: the present invention provides a technical solution, step S1, raw material preparation: weigh and prepare the raw materials according to the raw material components required by the preparation process, and the weighed raw materials include: 40wt% of polyethylene terephthalate of model Huizhou Nanya 4210G3, 11wt% of thermal insulation masterbatch, 10wt% of linear low-density polyethylene 1002, 8wt% of polyethylene naphthalate of TeonexQ65, 8wt% of thermoplastic polyurethane ShoreD55, 2wt% of sodium tripolyphosphate, 1wt% of antioxidant, 4wt% of Paraloid series thermoplastic polyacrylate resin, 1wt% of heat stabilizer, 3wt% of curing agent, 3wt% of coupling agent, 3wt% of low molecular weight polyethylene glycol 4000, 3wt% of lubricant and 3wt% of light stabilizer; Step S2, raw material pretreatment: adding 40wt% of Huizhou Nanya 4210G3 polyethylene terephthalate, 11wt% of thermal insulation masterbatch, 10wt% of linear low-density polyethylene 1002, 8wt% of TeonexQ65 polyethylene naphthalate, 8wt% of thermoplastic polyurethane ShoreD55, 2wt% of sodium tripolyphosphate, 4wt% of Paraloid series thermoplastic polyacrylate resin and 3wt% of low molecular weight polyethylene glycol 4000 to a mixing device for stirring and mixing; Step S3, material curing: adding 3 wt% of curing agent to the mixing device in step S2 for curing, the curing agent accelerates the curing of the mixed material, and adding 1 wt% of antioxidant during the curing process; Step S4, surface modification: adding 3 wt% of coupling agent to the mixture obtained in step S3, and performing surface modification on the mixture with 3 wt% of coupling agent, so as to obtain a mixture raw material with reduced viscosity; Step S5, cross-linking reaction: adding 3 wt% of a lubricant to the mixed raw material obtained in step S4, wherein 3 wt% of the lubricant causes the mixed raw material to undergo a cross-linking reaction to generate a smooth mixed raw material; Step S6, improving light transmittance: adding 3 wt% of light stabilizer and 1 wt% of heat stabilizer to the mixed raw material obtained in step S5 to improve the light transmittance of the mixed raw material; Step S7, granulation: conveying the mixture obtained in step S6 to an extruder for extrusion, and then pelletizing it through a pelletizer to obtain granular high-transmittance PET particles; Step S8, film forming: the high-transmittance PET particles obtained in step S7 are stretched transversely and longitudinally through a fully automatic vacuum drum, an extruder and a biaxial stretching unit to obtain a formed high-gloss PET film; Step S9, rolling and forming: cutting and trimming the high-gloss PET film dried in step S8, rolling up the cut high-gloss PET film and storing it, thereby completing the manufacturing of the high-gloss PET film.

[0028] The manufacturing method of the thermal insulation masterbatch is as follows: first prepare 60wt% of cesium tungstate powder, add 80wt% of the prepared cesium tungstate powder, 5wt% of Paraloid series thermoplastic polyacrylate resin and 7wt% of coupling agent into a mixing and stirring device, mix and stir evenly, feed the mixed material into an extruder, and extrude the material through the die head of the extruder after preheating, heating and melting, devolatilization and shearing, and then cool it into a solid state through a cooling device and enter a pelletizer for cutting to prepare the thermal insulation masterbatch.

[0029] The antioxidant is a mixture of tea polyphenols, tocopherol, butylated hydroxyanisole, butylated hydroxytoluene and tert-butylhydroquinone, and the mixing weight ratio of tea polyphenols, tocopherol and butylated hydroxyanisole, butylated hydroxytoluene and tert-butylhydroquinone is 1:2:1:1:1.

[0030] The mixing temperature of step S2 is controlled at 125° C., and the mixing time of step S2 is controlled at 1.1 h.

[0031] The light stabilizer is specifically a mixture of carbon black, titanium dioxide benzophenone and salicylate, and the mixing weight ratio of carbon black, titanium dioxide benzophenone and salicylate is 1:1:2.

[0032] The film forming temperature in step S8 is controlled at 110° C., and the high gloss PET film in step S9 needs to be cooled to below 25° C. before being rolled up.

[0033] The lubricant is a mixture of oleamide, erucamide and calcium stearate, and the weight ratio of oleamide, erucamide and calcium stearate is 1:2:1.

[0034] The coupling agent is specifically a mixture of silane coupling agent a151 and vinyl trimethoxy silane, and the mixing weight ratio of the silane coupling agent a151 and vinyl trimethoxy silane is 1:2.

[0035] The thermal stabilizer is triethyl phosphate.

[0036] The curing agent is a mixture of diaminodiphenylmethane, metaphenylenediamine and diaminodiphenyl sulfone, and the mixing weight ratio of diaminodiphenylmethane, metaphenylenediamine and diaminodiphenyl sulfone is 1:1:1.

[0037] Example 3 The difference from the above embodiment is that: the present invention provides a manufacturing process of a high-gloss PET film, step S1, raw material preparation: weighing and preparing raw materials according to the raw material components required by the preparation process, the weighed raw materials include: 30wt% of polyethylene terephthalate of model Huizhou Nanya 4210G3, 10wt% of thermal insulation masterbatch, 20wt% of linear low-density polyethylene 1002, 8wt% of polyethylene naphthalate of TeonexQ65, 9wt% of thermoplastic polyurethane ShoreD55, 2wt% of sodium tripolyphosphate, 2wt% of antioxidant, 4wt% of Paraloid series thermoplastic polyacrylate resin, 2wt% of heat stabilizer, 3wt% of curing agent, 3wt% of coupling agent, 3wt% of low molecular weight polyethylene glycol 4000, 1.5wt% of lubricant and 2.5wt% of light stabilizer; Step S2, raw material pretreatment: adding 30wt% of Huizhou Nanya 4210G3 polyethylene terephthalate, 10wt% of thermal insulation masterbatch, 20wt% of linear low-density polyethylene 1002, 8wt% of TeonexQ65 polyethylene naphthalate, 9wt% of thermoplastic polyurethane ShoreD55, 2wt% of sodium tripolyphosphate, 4wt% of Paraloid series thermoplastic polyacrylate resin, and 3wt% of low molecular weight polyethylene glycol 4000 to a mixing device for stirring and mixing; Step S3, material curing: adding 3wt% of curing agent to the mixing device in step S2 for curing, the curing agent accelerates the curing of the mixed material, and adding 2wt% of antioxidant during the curing process; Step S4, surface modification: adding 3 wt% of coupling agent to the mixture obtained in step S3, and performing surface modification on the mixture with 3 wt% of coupling agent, so as to obtain a mixture raw material with reduced viscosity; Step S5, cross-linking reaction: adding 1.5 wt% of a lubricant to the mixed raw material obtained in step S4, so that the mixed raw material undergoes a cross-linking reaction to generate a smooth mixed raw material; Step S6, improving light transmittance: adding 2.5 wt% of light stabilizer and 2 wt% of heat stabilizer to the mixed raw material obtained in step S5 to improve the light transmittance of the mixed raw material; Step S7, granulation: conveying the mixture obtained in step S6 to an extruder for extrusion, and then pelletizing it through a pelletizer to obtain granular high-transmittance PET particles; Step S8, film forming: the high-transmittance PET particles obtained in step S7 are stretched transversely and longitudinally through a fully automatic vacuum drum, an extruder and a biaxial stretching unit to obtain a formed high-gloss PET film; Step S9, rolling and forming: cutting and trimming the high-gloss PET film dried in step S8, rolling up the cut high-gloss PET film and storing it, thereby completing the manufacturing of the high-gloss PET film.

[0038] The manufacturing method of the thermal insulation masterbatch is as follows: first prepare 60wt% of cesium tungstate powder, add 80wt% of the prepared cesium tungstate powder, 5wt% of Paraloid series polyacrylate resin and 7wt% of coupling agent into a mixing and stirring device, mix and stir evenly, feed the mixed material into an extruder, and extrude the material through the die head of the extruder after preheating, heating and melting, devolatilization and shearing, and then cool it into a solid state through a cooling device and enter a pelletizer for cutting to prepare the thermal insulation masterbatch.

[0039] The antioxidant is a mixture of tea polyphenols, tocopherol, butylated hydroxyanisole, butylated hydroxytoluene and tert-butylhydroquinone, and the mixing weight ratio of tea polyphenols, tocopherol and butylated hydroxyanisole, butylated hydroxytoluene and tert-butylhydroquinone is 1:2:2:1:1.

[0040] The mixing temperature of step S2 is controlled at 130° C., and the mixing time of step S2 is controlled at 1.5 h.

[0041] The light stabilizer is specifically a mixture of carbon black, titanium dioxide benzophenone and salicylate, and the mixing weight ratio of carbon black, titanium dioxide benzophenone and salicylate is 2:1:2.

[0042] The film forming temperature in step S8 is controlled at 120° C., and the high gloss PET film in step S9 needs to be cooled to below 25° C. before being rolled up.

[0043] The lubricant is a mixture of oleamide, erucamide and calcium stearate, and the weight ratio of oleamide, erucamide and calcium stearate is 2:2:1.

[0044] The coupling agent is specifically a mixture of silane coupling agent a151 and vinyl trimethoxy silane, and the weight ratio of the silane coupling agent a151 and vinyl trimethoxy silane is 2:1.

[0045] The thermal stabilizer is triethyl phosphate.

[0046] The curing agent is a mixture of diaminodiphenylmethane and meta-phenylenediamine, and the mixing weight ratio of diaminodiphenylmethane to meta-phenylenediamine is 1:1.

[0047] Control group The difference from the above embodiment is that: Step S1, raw material preparation: weigh and prepare the raw materials according to the raw material components required by the preparation process, and the weighed raw materials include: 43.8wt% of polyethylene terephthalate of model Huizhou Nan Ya 4210G3, 11wt% of thermal insulation masterbatch, 10wt% of linear low-density polyethylene 1002, 8wt% of polyethylene naphthalate of TeonexQ65, 8wt% of thermoplastic polyurethane ShoreD55, 2wt% of sodium tripolyphosphate, 1wt% of antioxidant, 4wt% of Paraloid series thermoplastic polyacrylate resin, 3wt% of curing agent, 3wt% of coupling agent, 3wt% of low molecular weight polyethylene glycol 4000, 3wt% of lubricant and 0.2wt% of light stabilizer; Step S2, raw material pretreatment: adding 43.8wt% of Huizhou Nan Ya 4210G3 polyethylene terephthalate, 11wt% of thermal insulation masterbatch, 10wt% of linear low-density polyethylene 1002, 8wt% of TeonexQ65 polyethylene naphthalate, 8wt% of thermoplastic polyurethane ShoreD55, 2wt% of sodium tripolyphosphate, 4wt% of Paraloid series thermoplastic polyacrylate resin and 3wt% of low molecular weight polyethylene glycol 4000 to a mixing device for stirring and mixing; Step S3, material curing: adding 3 wt% of curing agent to the mixing device in step S2 for curing, the curing agent accelerates the curing of the mixed material, and adding 1 wt% of antioxidant during the curing process; Step S4, surface modification: adding 3 wt% of coupling agent to the mixture obtained in step S3, and performing surface modification on the mixture with 3 wt% of coupling agent, so as to obtain a mixture raw material with reduced viscosity; Step S5, cross-linking reaction: adding 3 wt% of a lubricant to the mixed raw material obtained in step S4, wherein 3 wt% of the lubricant causes the mixed raw material to undergo a cross-linking reaction to generate a smooth mixed raw material; Step S6, improving light transmittance: adding 0.2 wt% of a light stabilizer to the mixed raw material obtained in step S5 to improve the light transmittance of the mixed raw material; Step S7, granulation: conveying the mixture obtained in step S6 to an extruder for extrusion, and then pelletizing it through a pelletizer to obtain granular high-transmittance PET particles; Step S8, film forming: the high-transmittance PET particles obtained in step S7 are stretched transversely and longitudinally through a fully automatic vacuum drum, an extruder and a biaxial stretching unit to obtain a formed high-gloss PET film; Step S9, rolling and forming: cutting and trimming the high-gloss PET film dried in step S8, rolling up the cut high-gloss PET film and storing it, thereby completing the manufacturing of the high-gloss PET film.

[0048] The manufacturing method of the thermal insulation masterbatch is as follows: first prepare 60wt% of cesium tungstate powder, add 80wt% of the prepared cesium tungstate powder, 5wt% of Paraloid series polyacrylate resin and 7wt% of coupling agent into a mixing and stirring device, mix and stir evenly, feed the mixed material into an extruder, and extrude the material through the die head of the extruder after preheating, heating and melting, devolatilization and shearing, and then cool it into a solid state through a cooling device and enter a pelletizer for cutting to prepare the thermal insulation masterbatch.

[0049] The antioxidant is a mixture of tea polyphenols, tocopherol, butylated hydroxyanisole, butylated hydroxytoluene and tert-butylhydroquinone, and the mixing weight ratio of tea polyphenols, tocopherol and butylated hydroxyanisole, butylated hydroxytoluene and tert-butylhydroquinone is 1:2:1:1:1.

[0050] The mixing temperature of step S2 is controlled at 125° C., and the mixing time of step S2 is controlled at 1.1 h.

[0051] The light stabilizer is specifically a mixture of carbon black, titanium dioxide benzophenone and salicylate, and the mixing weight ratio of carbon black, titanium dioxide benzophenone and salicylate is 1:1:2.

[0052] The film forming temperature in step S8 is controlled at 110° C., and the high gloss PET film in step S9 needs to be cooled to below 25° C. before being rolled up.

[0053] The lubricant is a mixture of oleamide, erucamide and calcium stearate, and the weight ratio of oleamide, erucamide and calcium stearate is 1:2:1.

[0054] The coupling agent is specifically a mixture of silane coupling agent a151 and vinyl trimethoxy silane, and the mixing weight ratio of the silane coupling agent a151 and vinyl trimethoxy silane is 1:2.

[0055] The curing agent is a mixture of diaminodiphenylmethane, metaphenylenediamine and diaminodiphenyl sulfone, and the mixing weight ratio of diaminodiphenylmethane, metaphenylenediamine and diaminodiphenyl sulfone is 1:1:1.

[0056] The material ratio of the control group is different from that of Example 1, Example 2 and Example 3. The main difference lies in the weight ratio of the light stabilizer to the heat stabilizer in the control group. By comparing the light transmittance and thermal shrinkage of the PET film processed from the control group with those processed from Examples 1, Example 2 and Example 3, the improvement in the light transmittance of the material after the improved manufacturing process can be compared.

[0057] The material performance parameters prepared in the above implementation cases are measured by using a transmittance measuring instrument to measure the transmittance of the PET film. The specific measurement steps are as follows: turn on the machine and perform self-calibration. After displaying 100%, start the test. Put the PET film in the card slot of the fixed bracket. The test results are immediately displayed on the screen. Short press the "HOLD" key to lock the test data. Remove the PET film to view the data. The test personnel take 5 samples with a size of 120×120㎜ square from the products in Example 1, Example 2, Example 3 and the control group, and then draw mutually perpendicular markings of 100×100㎜ along the middle of the horizontal and vertical directions of the samples, and place the 5 samples with marked lines flat in a constant temperature box with a temperature of (150±1)℃. Take them out after 30 minutes, and after cooling to room temperature, measure the length of their marking lines, so as to calculate the thermal shrinkage of each sample, and finally take the arithmetic mean. The test results are as follows: Case Light transmittance Transverse heat shrinkage Longitudinal heat shrinkage Example 1 96% 0.5% 0.9% Example 2 97.5% 0.58% 0.95% Example 3 98% 0.6% 1.0% Control group 80% 7% 1.3% It can be seen from the data in the above table that the light transmittance of the PET film prepared by the present invention is significantly improved compared with the existing PET film in the control group, and the transverse heat shrinkage ratio does not exceed the industry standard of 0-1%, and the longitudinal shrinkage ratio does not exceed 1.5%, indicating that the light transmittance of the PET film is enhanced while ensuring that the heat shrinkage ratio meets the standard, so that the products processed from the PET film have excellent light transmittance, thereby being able to meet the high standards of existing electronic products and effectively improving the adaptability of the PET film.

[0058] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for manufacturing a high gloss PET film, characterized in that: The following steps are involved: Step S1, raw material preparation: weigh and prepare raw materials according to the raw material components required by the preparation process, and the weighed raw materials include: 30-50wt% of polyethylene terephthalate, 10-20wt% of thermal insulation masterbatch, 10-20wt% of polyethylene, 8-16wt% of polyethylene naphthalate, 8-15wt% of polyurethane, 2-6wt% of sodium tripolyphosphate, 1-5wt% of antioxidant, 4-14wt% of polyacrylate resin, 1-6wt% of heat stabilizer, 2-8wt% of curing agent, 2-7wt% of coupling agent, 2-10wt% of polyethylene glycol, 0.5-3wt% of lubricant and 0.5-5wt% of light stabilizer; Step S2, raw material pretreatment: adding 30-50wt% of polyethylene terephthalate, 10-20wt% of thermal insulation masterbatch, 10-20wt% of polyethylene, 8-16wt% of polyethylene naphthalate, 8-15wt% of polyurethane, 2-6wt% of sodium tripolyphosphate, 4-14wt% of polyacrylate resin and 2-10wt% of polyethylene glycol to a mixing device for stirring and mixing; Step S3, material curing: adding 2-8 wt% of curing agent to the mixing device in step S2 for curing, the curing agent accelerates the curing of the mixed material, and adding 1-5 wt% of antioxidant during the curing process; Step S4, surface modification: adding 2-7 wt% of coupling agent to the mixture obtained in step S3, and performing surface modification on the mixture with 2-7 wt% of coupling agent, so as to obtain a mixture raw material with reduced viscosity; Step S5, cross-linking reaction: adding 0.5-3 wt% of a lubricant to the mixed raw material obtained in step S4, so that the mixed raw material undergoes a cross-linking reaction to generate a smooth mixed raw material; Step S6, improving light transmittance: adding 0.5-5wt% of light stabilizer and 1-6wt% of heat stabilizer to the mixed raw material obtained in step S5 to improve the light transmittance of the mixed raw material; Step S7, granulation: conveying the mixture obtained in step S6 to an extruder for extrusion, and then pelletizing it through a pelletizer to obtain granular high-transmittance PET particles; Step S8, film forming: the high-transmittance PET particles obtained in step S7 are stretched transversely and longitudinally through a fully automatic vacuum drum, an extruder and a biaxial stretching unit to obtain a formed high-gloss PET film; Step S9, rolling and forming: cutting and trimming the high-gloss PET film dried in step S8, rolling up the cut high-gloss PET film and storing it, thereby completing the manufacturing of the high-gloss PET film.

2. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The manufacturing method of the thermal insulation masterbatch is as follows: first prepare 60wt% of cesium tungstate powder, add 80wt% of the prepared cesium tungstate powder, 5wt% of polyacrylate resin and 7wt% of coupling agent into a mixing and stirring device, mix and stir evenly, feed the mixed material into an extruder, and extrude the material through the die head of the extruder after preheating, heating and melting, devolatilization and shearing, and then cool it into a solid state through a cooling device and enter a pelletizer for cutting to prepare the thermal insulation masterbatch.

3. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The antioxidant is selected from any one or more of tea polyphenols, tocopherol, butylated hydroxyanisole, butylated hydroxytoluene or tert-butylhydroquinone.

4. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The mixing temperature of step S2 is controlled between 125° C. and 150° C., and the mixing time of step S2 is controlled between 1 h and 1.5 h.

5. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The light stabilizer is specifically one or more of carbon black, titanium dioxide benzophenone, salicylic acid ester and benzotriazole.

6. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The film forming temperature in step S8 is controlled between 100° C. and 120° C., and the high gloss PET film in step S9 needs to be cooled to below 25° C. before being rolled up.

7. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The lubricant is selected from any one or more of oleamide, erucamide, calcium stearate and silicone.

8. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The coupling agent is specifically a mixture of silane coupling agent a151 and vinyl trimethoxy silane, and the mixing weight ratio of the silane coupling agent a151 and vinyl trimethoxy silane is 1:

1.

9. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The thermal stabilizer is triethyl phosphate.

10. The manufacturing process of the high gloss PET film according to claim 1, characterized in that: The curing agent is one or more of diaminodiphenylmethane, m-phenylenediamine and diaminodiphenyl sulfone.

Citation Information

Patent Citations

  • Antistatic smooth glass-fiber-added polyethylene glycol terephthalate and preparation method thereof

    CN103881322A

  • High-heat-resistance and high-light-transmittance PET film

    CN114106528A

  • High-heat-insulation and high-light-transmittance PET optical film and preparation method thereof

    CN118374041A